Thomas Henry Carter, The Laws of Alaska : Embracing the Penal Code, the Code of Criminal Procedure, the Political Code, the Code of Civil Procedure, and the Civil Code, with the Treaty of Cession, and All Acts and Parts of Acts Relating to the District : Annotated with References to Decisions by the Courts of the United States and the Supreme Court of Oregon 5 (1900) - (:unkn) unknown (My University, 1900)
§ 21: Prohibited the assault or beating of another with a cowhide, whip, stick, while being armed with a pistol, dirk, or other deadly weapon, with intent to intimidate or prevent such other from resisting or defending himself. Violators punished by imprisonment not more than ten nor less than one year.
Keywords: CARRY - INTENT TO COMMIT CRIME